Interações discursivas, práticas e movimentos epistêmicos no ensino de relatividade restrita - Neves, Jefferson Adriano (2020)
In this work, we analyze and comprehend the discursive interactions that emerge in the classroom during the realization of a teaching sequence on the concepts of space and time according to the Theory of Special Relativity, and identify the epistemic practices mobilized by students and the role of the teacher in this process, in order to answer the following research problems: Introductory classes in Theory of Special Relativity designed to encourage discursive interactions support the development of which epistemic practices? What discursive and epistemic actions of the teacher support or not the development of such practices? What discursive and epistemic actions of the teacher support or not the development of such practices? Epistemic practices are those that are socially organized, standardized and performed in an interactive way, in which the members of a community propose, justify, evaluate and legitimize knowledge. In the field of science education, several authors argue that learning science is related to learning scientific and epistemic practices. The designed sequence for this research context was performed with students who were studying in the first semester of the Physics Degree course in 2018. The investigation took place in the classroom space, with all activities recorded in audio and video, and described in the form of a field diary. The written activities that were written by the students were also part of the process. With the collected material, we organized seven teaching episodes that were transcribed and analyzed using the Argumentative Processes and Products and Practices and Epistemic Movements. In order to investigate Epistemic Practices, we proposed a set of practices specifically related to Modern and Contemporary Physics. The proposed instrument is composed of 13 practices organized in the social instances of Sense Production, Communication and Knowledge Assessment. In the analysis, we identified the student involvement in nine epistemic practices. This process had a high degree of inference and the context was essential in distinguishing between practices. Another fundamental element in carrying out the sequence was the teacher and his actions throughout the episodes, which were modified according to the problem situation or due to the pedagogical objectives. In the discursive interactions, present in the episodes, we reconstructed 17 arguments that were influenced, to a greater or lesser degree, by the teacher's actions.